Critical regionalism : Connecting Politics and Culture in the American Landscape. - Powell, Douglas Reichert (The University of North Carolina Press, 2012)
The idea of ""region"" in America has often served to isolate places from each other, observes Douglas Reichert Powell. Whether in the nostalgic celebration of folk cultures or the urbane distaste for ""hicks, "" certain regions of the country are identified as static, insular, and culturally disconnected from everywhere else. In Critical Regionalism, Reichert Powell explores this trend and offers alternatives to it. Reichert Powell proposes using more nuanced strategies that identify distinctive aspects of particular geographically marginal communities without turning them into peculiar ""hick.